Coating induced residual stress in nonoriented electrical steel laminations. Issue 16 (28th August 2014) - Ding, Yaoyao; Gallaugher, Matthew; Brodusch, Nicolas; Gauvin, Raynald; Chromik, Richard R.
Abstract: Abstract : To produce the magnetic core of electric motors, nonoriented electrical steels (NOESs) are used with an electrically insulating coating applied to the surface. Residual stress is induced during the coating process, which will alter the hardness and magnetic domain structure of the NOES. In this study, the effect of the coating is examined, specifically, its role in creating a residual stress near the coating/steel interface. This stress was investigated by the nanoindentation technique. With this method, a ∼30 µm deep affected area was observed for NOES along both the rolling and transverse cross section directions, when in the presence of the coating. A biaxial tensile stress of ∼200 MPa was calculated from the measured hardness values in the NOES, which was linked to variations in the magnetic domain structure near the interface. The observed magnetic domain structure was simplified by the reduction of supplemental domain structure near the coating/steel interface.